# Induction on Lists

It turns out that natural numbers and lists are quite similar, when viewed as data types. Here are the definitions of both, side-by-side for comparison:

type 'a list =                  type nat =
| []                            | Z
| (::) of 'a * 'a list          | S of nat


Both types have a constructor representing a concept of "nothing". Both types also have a constructor representing "one more" than another value of the type: S n is one more than n, and h :: t is a list with one more element than t.

The induction principle for lists is likewise quite similar to the induction principle for natural numbers. Here is the principle for lists:

forall properties P,
if P([]),
and if forall h t, P(t) implies P(h :: t),
then forall lst, P(lst)


An inductive proof for lists therefore has the following structure:

Proof: by induction on lst.
P(lst) = ...

Base case: lst = []
Show: P([])

Inductive case: lst = h :: t
IH: P(t)
Show: P(h :: t)


Let's try an example of this kind of proof. Recall the definition of the append operator:

let rec append lst1 lst2 =
match lst1 with
| [] -> lst2
| h :: t -> h :: append t lst2

let (@) = append


We'll prove that append is associative.

Theorem: forall xs ys zs, xs @ (ys @ zs) = (xs @ ys) @ zs

Proof: by induction on xs.
P(xs) = forall ys zs, xs @ (ys @ zs) = (xs @ ys) @ zs

Base case: xs = []
Show: forall ys zs, [] @ (ys @ zs) = ([] @ ys) @ zs

[] @ (ys @ zs)
=   { evaluation }
ys @ zs
=   { evaluation }
([] @ ys) @ zs

Inductive case: xs = h :: t
IH: forall ys zs, t @ (ys @ zs) = (t @ ys) @ zs
Show: forall ys zs, (h :: t) @ (ys @ zs) = ((h :: t) @ ys) @ zs

(h :: t) @ (ys @ zs)
=   { evaluation }
h :: (t @ (ys @ zs))
=   { IH }
h :: ((t @ ys) @ zs)

((h :: t) @ ys) @ zs
=   { evaluation of inner @ }
(h :: (t @ ys)) @ zs
=   { evaluation of outer @ }
h :: ((t @ ys) @ zs)

QED